2023
DOI: 10.32471/exp-oncology.2312-8852.vol-43-no-2.16096
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of apigenin with doxorubicin enhances anti-migration and antiproliferative effects via PI3K/PTEN/AKT pathway in prostate cancer cells

Abstract: Summary. Prostate cancer is one of the leading cancers in men, and new approaches are needed for its treatment. The aim of this study was to investigate the effect of co-administration of naturally occurring flavone apigenin and doxorubicin to androgen-insensitive prostate cancer cells. Methods: The effect of the treatment on survival and migration of human PC3 cells was evaluated by MTT and scratch assay, respectively. Apoptosis and cell cycle distribution were detected by image-based cytometry. mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The changes in the cell cycle regulation in tumor patterns can cause cellular proliferation. The rapid proliferation that resulted in the series and extension of tissue accumulation can be used to identify a significant basic origin of cancer succession ( Ayyildiz et al, 2021 ; Kubczak, Szustka & Rogalinska, 2021 ). The MTT assay results indicated that AgNPs, CuONPs, and polymeric PVP-Ag–CuO NCS were effective against HepG2 cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the cell cycle regulation in tumor patterns can cause cellular proliferation. The rapid proliferation that resulted in the series and extension of tissue accumulation can be used to identify a significant basic origin of cancer succession ( Ayyildiz et al, 2021 ; Kubczak, Szustka & Rogalinska, 2021 ). The MTT assay results indicated that AgNPs, CuONPs, and polymeric PVP-Ag–CuO NCS were effective against HepG2 cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced Bcl-2 and Bcl-xL levels, as well as a rise in the active form of the Bax protein, were linked to these apigenin aftereffects [19]. Apigenin as well as doxorubicin dose-dependently inhibited cell survival, and co-administration of both compound meaningfully induced cell death through downregulating Bcl-XL and upregulating the mRNA expression of caspases, Bax and cytochrome c [92].…”
Section: Prostate Cancermentioning
confidence: 99%
“…In vivo apigenin treatment significantly increased the tumor size [82] Lung cancer Apigenin sensitized lung cancer cells to TRAIL-induced apoptosis through upregulating the levels of death receptor 4 and death receptor 5 [28] Oral cancer The anticancer potential of apigenin in an oral squamous cell carcinoma was noted, proposing that it may be a very hopeful chemopreventive agent [83] Lymphoma Apigenin leads to an important reduction of the expression of pro-proliferative pathways in mTOR/PI3K to inhibit cancer cell survival [84] Lymphoma Apigenin activated p53 that induced catalase, a reactive oxygen species scavenger enzyme, and inhibited the signal transducer and activator of transcription 3 [52] Skin cancer Apigenin inhibited cell migration, invasion and induced G2/M phase arrest and apoptosis [85] Mesothelioma API-induced apoptosis was continued by the increase of Bax/Bcl-2 ratio, activation of both caspase 9 and caspase 8 and the increase of p53 expression, [86] Adenoid cystic carcinoma-Apigenin inhibits carcinoma-2 cell growth in a dose-and time-dependent way. Treatment with apigenin also induced apoptosis and G 2 /M-phase arrest in a dose-and time-dependent fashion [87] Myeloma Apigenin treatment downregulated the expression of the antiapoptotic proteins and survivin that finally induced apoptosis in multiple myeloma cells [88] Leukemia Apigenin is a potential chemo-preventive agent due to the induction of leukemia cell-cycle arrest [89] Leukemia Administration of apigenin resulted in attenuation of tumor growth in xenografts U937 convoyed inactivation of Akt as well as activation of JNK [90] Prostate cancer Apigenin suppressed the proliferation as well as inhibited the migration and invasive in a dose-and time-dependent way [91] Prostate cancer Apigenin treatment caused the significant decrease in cell viability and the induction of apoptosis [92] Prostate cancer Apigenin caused cell cycle arrest [93] Osteosarcoma Apigenin meaningfully decreased cell viability and efficiently induced apoptosis via the activations of caspase and BAX [94] Osteosarcoma Apigenin inhibits the tumor growth of osteosarcoma cells via inactivating Wnt/β-catenin signaling [55] Thyroid cancer Apigenin synergizes with TRAIL via the regulation of Bcl2 family proteins [95] Thyroid cancer Apigenin enhanced production of reactive oxygen species following the induction of significant damage of DNA [96] Brain cancer The glioblastoma stem cell inhibition effect of apigenin may be caused via the downregulation of the c-Met signaling pathway [97] Brain cancer Downregulation of miR-423-5p enhances the sensitivity of glioma stem cells to apigenin through the mitochondr...…”
Section: Esophagus Cancermentioning
confidence: 99%
“…It may be beneficial to combine apigenin and doxorubicin as a therapeutic approach to reduce cancer cell migration and proliferation, which are linked to metastasis and tumor formation. Study by Ayyildiz et al, suggested that the natural flavone apigenin and the chemotherapy drug doxorubicin would be effective in treating castration‐resistant prostate cancer (Ayyildiz et al, 2021). Together, these results highlight the fact that apigenin directly inhibits the expression of AKT, hence preventing tumor cell growth in several human malignancies.…”
Section: Cancer Therapeutic Potential Of Apigeninmentioning
confidence: 99%